2016
DOI: 10.1177/1524838015585313
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review on Post-Traumatic Stress Disorder Among Survivors of the Wenchuan Earthquake

Abstract: Post-traumatic stress disorder (PTSD) widely occurs among victims or witness of disasters. With flashbacks, hyperarousal, and avoidance being the typical symptoms, PTSD became a focus of psychological research. The earthquake in Wenchuan, China, on May 12, 2008, was without precedent in magnitude and aftermath and caused huge damage, which drew scientists' attention to mental health of the survivors. We conducted a systematic overview by collecting published articles from the PubMed database and classifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
64
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 182 publications
(303 reference statements)
5
64
0
1
Order By: Relevance
“…First, the high degree of trauma exposure predicted high levels of PTSD symptoms but not depressive symptoms. The dose-effect relationship of trauma exposure to PTSD symptoms has been supported by many previous studies (Hong & Efferth, 2016). However, trauma exposure had no statistically significant effect on depressive symptoms in our study.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…First, the high degree of trauma exposure predicted high levels of PTSD symptoms but not depressive symptoms. The dose-effect relationship of trauma exposure to PTSD symptoms has been supported by many previous studies (Hong & Efferth, 2016). However, trauma exposure had no statistically significant effect on depressive symptoms in our study.…”
Section: Discussionsupporting
confidence: 61%
“…Children and adolescents are easily exposed to second-hand trauma (TV and nonprofessional psychological first aid), which has been shown to increase the risk of PTSD among adolescents (Yeung et al, 2016). In contrast, a systematic review of PTSD reactions after the Wenchuan earthquake showed that children and adolescents had a lower prevalence of PTSD and that their symptoms lasted for a much shorter period than did those of adults (Hong & Efferth, 2016). These findings could influence the different relationships between PTSD and depression in children and adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, the long lasting effects on sleep have been investigated by rather few longitudinal studies. 6,14,13,23 In this context, various predictive factors of sleep disturbances have been investigated, such as proximity to the earthquake's epicenter, extent of material and human losses, socio-demographic characteristics, and coexisting psychopathology (anxiety, depression, and PTSD symptoms in particular).…”
Section: Discussionmentioning
confidence: 99%
“…12 Immediate and short-term post-trauma sleep problems have been often reported in the literature but only a few studies have investigated sleep complaints several months following a natural disaster. 13,14 In the present study we assessed sleep problems, insomnia in particular, in the affected population of Cephalonia, retrospectively one month before and 6 months after the earthquake, and investigated their correlation with depression, anxiety and PTSD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…It has been calculated that life time prevalence of PTSD in adults is 7.8%, while women have higher risk than men (20.4 vs. 8.2%) despite experiencing fewer traumas (Kessler et al, 2005; Ditlevsen and Elklit, 2012). Pre-trauma factors, such as lower socioeconomic status, parental neglect and poor social support increase the risk (Hong and Efferth, 2015). In addition, more and more studies reported the correlation between PTSD and other physiological diseases, such as diabetes (Agyemang et al, 2012), cancer (Abbey et al, 2015) and cardiovascular diseases (Boscarino, 2008), or psychiatric diseases, such as depression and anxiety (Farr et al, 2014).…”
Section: Discussionmentioning
confidence: 99%